Surface treatment liquid, method for treating the surface of copper, method for bonding copper and tin, and method for producing

By using a surface treatment liquid containing water-soluble copper salts, thio compounds and nitrogen-containing alkali compounds to treat the copper surface and perform hot press bonding, the problem of insufficient bonding strength between copper and tin is solved, and efficient and stable copper-tin is achieved. Formation of the joint.

CN119487237APending Publication Date: 2025-02-18MEC CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380051198.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-13
Filing Date
2023-06-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art has the problem of insufficient bonding strength during the bonding process between copper and tin, making it difficult to achieve efficient and stable bonding.

Method used

A surface treatment liquid containing a water-soluble copper salt, a thio compound and a nitrogen-containing alkali compound is used to form a copper-tin bond during the hot pressing process.

Benefits of technology

The bonding strength between copper and tin is significantly improved, and a more efficient bonding process is achieved, ensuring the stability and robustness of the copper-tin bonding body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005220834540000031
    Figure BDA0005220834540000031
  • Figure BDA0005220834540000061
    Figure BDA0005220834540000061
  • Figure BDA0005220834540000062
    Figure BDA0005220834540000062
Patent Text Reader

Abstract

The invention relates to a surface treatment liquid, which is an aqueous solution and comprises a water-soluble copper salt; a thio compound having a structure in which one or more nitrogen atoms and one or more sulfur atoms are covalently bonded to one carbon atom; and one or more nitrogen-containing base compounds selected from the group consisting of basic amino acids, guanidine compounds, and quaternary ammonium salts. The concentration of the water-soluble copper salt in the surface treatment liquid is preferably 0.05 mM to 70 mM, and the concentration of the thio compound is preferably 0.005 mM to 20 mM. By bringing the surface treatment liquid into contact with the surface of the copper, the tin bondability can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a copper surface treatment liquid and a copper surface treatment method, and also to a copper and tin bonding method and a bonding body manufacturing method. Background Art

[0002] In semiconductors and printed circuit boards, the surface of copper, which is a conductor, is bonded to another substrate, electronic components, insulators, etc. There are several proposals for methods of performing surface treatment on copper to improve bonding strength when bonding another member to the surface of copper.

[0003] For example, Patent Document 1 states that the adhesion to the resin layer can be improved by forming an alloy layer of copper and tin on the surface of copper. Patent Document 2 states that the surface of copper is treated with a solution containing copper ions and a silane coupling agent to form a coating film, thereby improving the adhesion to the resin layer.

[0004] In flip chip bonding, the copper bumps of the substrate are sometimes bonded to the tin electrodes of the chip by thermal compression. In this case, the bonding to the tin electrodes is improved by forming a tin plating layer or a nickel / gold plating layer on the surface of the copper bumps. In addition, the bonding is sometimes improved by applying a flux or other surface treatment. (For example, see Patent Document 3).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2008-109111.

[0008] Patent document 2: Japanese Patent Application Publication No. 2022-020415.

[0009] Patent document 3: Japanese Patent Application Publication No. 2021-190473. Summary of the invention

[0010] Problems to be solved by the invention

[0011] An object of the present application is to provide a copper surface treatment solution for easily bonding copper and tin.

[0012] Technical solutions to problems

[0013] The surface treatment liquid of the present application is an aqueous solution, comprising: a water-soluble copper salt; a thio compound having a structure in which one or more nitrogen atoms and one or more sulfur atoms are covalently bonded to one carbon atom; and a nitrogen-containing base compound, which is one or more selected from a basic amino acid, a guanidine compound, and a quaternary ammonium salt. The concentration of the water-soluble copper salt in the surface treatment liquid is preferably 0.05mM to 70mM, and the concentration of the thio compound is preferably 0.005mM to 20mM.

[0014] The surface of copper is treated by bringing the solution into contact with the surface of copper, and copper and tin are bonded by thermally pressing a tin member onto the treated surface.

[0015] Effects of the Invention

[0016] By surface treating copper or copper alloy using the surface treatment solution of the present application, the bonding property to tin can be improved. DETAILED DESCRIPTION

[0017] [Surface treatment liquid]

[0018] The surface treatment liquid of the present application is used to improve the bonding property of tin to copper surface. The surface treatment liquid is an aqueous solution, comprising: a water-soluble copper salt; a thio compound having a specific structure; and one or more nitrogen-containing organic compounds selected from basic amino acids, guanidine compounds, and quaternary ammonium salts.

[0019] <Water-soluble copper salt>

[0020] Water-soluble copper salts dissolve in water to release divalent copper ions. Examples of water-soluble copper salts include copper sulfate, copper nitrate, copper chloride, copper acetate, copper sulfide, copper cyanide, copper ammonium chloride, copper gluconate, copper tartrate, copper perchlorate, and hydrates of these water-soluble copper salts. From the viewpoints of handling, cost, and raw material supply, copper sulfate, copper nitrate, copper chloride, and copper acetate are preferred.

[0021] <Thio compounds>

[0022] The surface treatment liquid contains a thio compound having a structure in which one or more nitrogen atoms and one or more sulfur atoms are covalently bonded to one carbon atom.

[0023] The structure in which one or more nitrogen atoms and one or more sulfur atoms are covalently bonded to one carbon atom may also have elements other than nitrogen and sulfur (hydrogen, carbon, oxygen, etc.) bonded to one carbon atom, or may have only one or more nitrogen atoms and one or more sulfur atoms bonded to one carbon atom.

[0024] From the viewpoint of forming a copper surface with excellent bonding properties to tin, the thio compound preferably has a structure in which only a nitrogen atom and a sulfur atom are covalently bonded to one carbon atom. Examples of the structure in which only a nitrogen atom and a sulfur atom are covalently bonded to one carbon atom include: structures in which one nitrogen atom and one sulfur atom are bonded to one carbon atom as shown in (A) and (B) below; structures in which two nitrogen atoms and one sulfur atom are bonded to one carbon atom as shown in (C) and (D) below; and structures in which one nitrogen atom and two sulfur atoms are bonded to one carbon atom as shown in (E) and (F) below.

[0025]

[0026] Examples of the thio compound including the structure (A) include isothiocyanates such as methyl isothiocyanate, ethyl isothiocyanate, propyl isothiocyanate, isopropyl isothiocyanate, butyl isothiocyanate, isobutyl isothiocyanate, cyclohexyl isothiocyanate, allyl isothiocyanate, 3-buten-1-yl isothiocyanate, ethoxycarbonyl isothiocyanate, 2-chloroethyl isothiocyanate, 3-methylthiopropyl isothiocyanate, 1-adamantyl isothiocyanate, phenyl isothiocyanate, benzyl isothiocyanate, benzoyl isothiocyanate, 3-pyridyl isothiocyanate, 1-naphthyl isothiocyanate, and 1,4-phenylene diisothiocyanate.

[0027] Examples of the thio compound including the structure (B) include thiocyanates such as sodium thiocyanate, potassium thiocyanate, ammonium thiocyanate, lithium thiocyanate, and copper thiocyanate; and thiocyanates such as methyl thiocyanate, ethyl thiocyanate, benzyl thiocyanate, and guanidine thiocyanate.

[0028] Examples of the thio compound including the structure (C) include isothiourea, isothiourea derivatives such as S-ethylisothiourea, 2-(cyanomethyl)isothiourea, S-(benzylthio)isothiourea, and S-ethylisothiourea hydrobromide, and salts thereof, and thiourea dioxide.

[0029] The thio compound containing the structure of (C) may be a compound in which -NC=N-, -NCS-, or -N=CS- forms a ring structure. Specific examples of the compound containing the structure of (C) and in which -NC=N- forms a ring structure include 2-mercapto-1H-imidazole, 2-mercapto-1-methylimidazole, 2-mercaptobenzimidazole and its derivatives, 2-mercaptopyrimidine and its derivatives, thiocyanate and its salts, 2-thiobarbituric acid, 3-amino-5-mercapto-1,2,4-triazole, 5-mercapto-1-methyltetrazolyl, 5-mercapto-1-phenyltetrazolyl, 6-amino-2-thionyl-1,2-dihydroxypyrimidin-4(3H)-one, and the like.

[0030] Examples of the thio compound including the structure (D) include thiourea; thiourea derivatives such as 1-methylthiourea, 1,3-dimethylthiourea, 1,3-diethylthiourea, 1,3-dipropylethylthiourea, 1,3-diisopropylthiourea, 1,3-dibutylthiourea, formamidinethiourea, 1,3-diphenylthiourea, tetramethylthiourea, ethylenethiourea, 1-phenylthiourea, 1,3-diphenylthiourea, 1,3-dicyclohexylthiourea, 1-allylthiourea, formamidinethiourea, thiosemicarbazide, and thioacetazone.

[0031] The thio compound containing the structure of (D) may also be a compound in which the -NCN- portion or the -NC=S- portion forms a ring structure. Specific examples of the compound in which the -NCN- portion forms a ring structure include: 2-thiouracil and its derivatives, 2,6-dimercaptopurine, etc. In addition, the compound containing the structure of (C) and the -NC=N- portion having a ring structure may become a compound containing the structure of (D) and the -NCN- portion forming a ring structure through tautomerism.

[0032] Examples of the thio compound including the structure (E) include N-cyanoimido-S,S-dimethyl-dithiocarbonate, cyanoimidodithiocarbonic acid monomethyl ester monopotassium salt, and N-[dimethylthiomethylene]-p-toluenesulfonamide.

[0033] The thio compound containing the structure of (E) may also be a -N=CS- portion or a -SCS- portion forming a ring structure. Specific examples of the compound having a -N=CS- portion forming a ring structure include bismuthiothiol, 2-mercaptothiazoline, thiazole-2-thiol, 2-mercaptobenzothiazole, 2-(methylthio)-2-thiazoline, 5-methyl-1,3,4-thiadiazole-2-thiol, 2-amino-5-mercapto-1,3,4-thiadiazole, and 2-mercapto-5-methylthio-1,3,4-thiadiazole.

[0034] Examples of the thio compound including the structure (F) include dimethyl dithiamine formate salts; diethyl dithiamine formate salts; dimethyl dithiamine formate esters such as methyl dimethyl dithiamine formate and benzyl dimethyl dithiamine formate; diethyl dithiamine formate esters such as methyl diethyl dithiamine formate and benzyl diethyl dithiamine formate; thiuram compounds such as tetramethyl thiuram monosulfide, tetramethyl thiuram disulfide, tetraethyl thiuram disulfide, tetrabutyl thiuram disulfide, tetraisopropyl thiuram disulfide, tetrabenzyl thiuram disulfide, and dipentylene thiuram tetrasulfide; S-(N,N-dimethylthiocarbamoyl)thioglycolic acid, 1-pyrrolidine dithiocarboxylic acid ammonium, methyl (phenyl) amino dithiocarboxylic acid cyanomethyl ester, 1-pyrrolidine dithiocarboxylic acid allyl ester, and p-xylenebis(diaminethiocarboxylic acid N,N-diethyl ester).

[0035] The thio compound containing the structure (F) may be a -NCS- portion, a -NC=S- portion, or a -SC=S- portion forming a ring structure. Specific examples of compounds having a -NCS portion forming a ring structure include rhodanine and its derivatives, 1,3-thiazinane-2-thione, and 2-thionyl-3-aminothiazol-4-one.

[0036] Among the above (A) to (F), (A) to (D) in which one sulfur atom is bonded to a carbon atom are particularly preferred.

[0037] <Nitrogen-containing basic compounds>

[0038] The surface treatment liquid contains a nitrogen-containing base compound in addition to the water-soluble copper salt and the thio compound. Examples of the nitrogen-containing base compound include basic amino acids, guanidine compounds, and quaternary ammonium salts.

[0039] (Basic Amino Acid)

[0040] Basic amino acids are amino acids having an isoelectric point greater than 7, and specific examples thereof include arginine, histidine, lysine, citrulline, ornithine, and hydroxylysine.

[0041] (Guanidane compound)

[0042] The guanidine compound is a compound having a guanidine group, and specific examples thereof include: guanidine salts such as guanidine carbonate, guanidine phosphate, guanidine hydrochloride, guanidine hydrobromide, guanidine hydroiodide, guanidine nitrate, guanidine sulfate, guanidine sulfonate, and guanidine thiocyanate; guanidine urea salts such as guanidine urea carbonate, guanidine urea phosphate, guanidine urea hydrochloride, guanidine urea nitrate, and guanidine urea sulfate; amine guanidine salts such as amineguanidine bicarbonate, amineguanidine nitrate, amineguanidine hydrochloride, and amineguanidine hemisulfate; salts of guanidine derivatives such as 1-methylguanidine sulfate, 1,1-dimethylguanidine sulfate, 1,1-diethylguanidine sulfate, 1,3-diphenylguanidine sulfate, 1-octadecylguanidine hydrochloride, and 1-(2-methyl-5-nitrophenyl)guanidine nitrate; and 1,3-diaminoguanidine salts. salts of amine guanidine derivatives such as 1-(5-nitrofuranylmethyl)amineguanidine hydrochloride; 1,1,3,3-tetramethylguanidine, 2-tert-butyl-1,1,3,3-tetramethylguanidine, phenylguanidine, 1,3-diphenylguanidine, 1,2,3-triphenylguanidine, nitroguanidine, 1-acetylguanidine, acetylacetonatoguanidine, 1-(tert-butyloxycarbonyl)guanidine, 1,3-bis(tert-butyloxycarbonyl)-2-(trifluoromethanesulfonyl)guanidine, 1,2,3-tri(tert-butyloxycarbonyl)guanidine, creatine, cyanoguanidine, sulfaguanidine, nitrosoguanidine, cimetidine, dinotefuran, 1-methyl-3-nitro-1-nitrosoguanidine, 1,3-di-o-tolylguanidine, 1-methyl-3-nitroguanidine, 1-(4-cyanophenyl)guanidine, etc.

[0043] (Quaternary ammonium salt)

[0044] Examples of the quaternary ammonium salt include tetraalkylammonium salts such as tetramethylammonium salt, tetraethylammonium salt, ethyltrimethylammonium salt, and N,N,N-trimethyl-1-adamantylammonium salt; trialkylmonoarylammonium salts such as trimethylphenylammonium salt and benzyltrimethylammonium salt; dialkylpiperidinium salts such as 1,1-dimethylpiperidinium salt, 1-ethyl-1-methylpiperidinium salt, 1-methyl-1-propylpiperidinium salt, and 1-butyl-1-methylpiperidinium salt; dialkylpyrrolidinium salts such as 1,1-dimethylpyrrolidinium salt, 1-ethyl-1-methylpyrrolidinium salt, 1-methyl-1-propylpyrrolidinium salt, and 1-butyl-1-methylpyrrolidinium salt; choline derivatives such as choline, choline chloride, and acetylcholine chloride; betaine anhydride, betaine hydrochloride, carnitine, and the like.

[0045] As the counter anion of the quaternary ammonium salt, there are: Cl - Br - ,I - 、ClO4 - 、BF4 - 、CH3COO - PF6 - 、HSO4 - 、C2H5SO4 - .

[0046] The quaternary ammonium salt may be a compound having a polymerizable functional group such as methacryloylcholine chloride, glycidyltrimethylammonium chloride, trimethylvinylammonium chloride, trimethylaminoethyl methacrylate·methylsulfate, diallyldimethylammonium chloride, and diallylmethylethylammonium ethylsulfate.

[0047] The quaternary ammonium salt may also be a polymer having a quaternary ammonium group (quaternary ammonium salt type polymer). The weight average molecular weight of the quaternary ammonium salt type polymer is preferably above 1000, and may also be above 2000 or above 3000. From the viewpoint of water solubility, the weight average molecular weight of the quaternary ammonium salt type polymer is preferably below 5 million, more preferably below 2 million.

[0048] Examples of the quaternary ammonium salt type polymer include polymers of quaternary ammonium salts having the above-mentioned polymerizable functional groups. Specific examples of the quaternary ammonium salt type polymer include polymers having a repeating unit represented by the following formula (I).

[0049]

[0050] In formula (I), R 1 To R 3 are independently a chain or cyclic hydrocarbon group which may have a substituent, R 1 To R 3 Two or more of them may be bonded to each other to form a ring structure. 4 is a hydrogen atom or a methyl group, X 1 is a single bond or a divalent linking group, Z - is the relative anion.

[0051] Specific examples of the polymer having a repeating unit represented by the formula (I) include quaternary ammonium salt-type styrene polymers and quaternary ammonium salt-type aminoalkyl (meth)acrylates.

[0052] The quaternary ammonium salt type polymer is represented by the following formula (II), and may have a repeating unit in which the carbon atoms in the main chain and the quaternary ammonium group form a ring structure.

[0053]

[0054] In the formula (II), R 5 and R 6 is a chain or cyclic hydrocarbon group which may have a substituent, R 5 and R 6 They may bond to each other to form a ring structure. m is an integer from 0 to 2. 2 and X 3Each independently represents a single bond or a divalent linking group. Specific examples of the polymer having a repeating unit of the general formula (II) include a quaternary ammonium salt type diallylamine polymer obtained by polymerizing a diallyldialkylammonium salt represented by the formula (IIa).

[0055]

[0056] In the formula (IIa), R 7 and R 8 Each of them is independently a hydrogen atom or a chain or cyclic hydrocarbon group which may have a substituent, and a hydrogen atom is preferred.

[0057] YuX 1 To X 3 In the case of a divalent linking group, specific examples thereof include: a methylene group, an alkylene group having 2 to 10 carbon atoms, an arylene group, a -CONH-R- group, a -COO-R- group (however, R is a single bond, a methylene group, an alkylene group having 2 to 10 carbon atoms, or an ether group (alkoxyalkyl group) having 2 to 10 carbon atoms), etc.

[0058] The quaternary ammonium salt type polymer may also be a copolymer. The quaternary ammonium salt type polymer may be a copolymer of a monomer containing a quaternary ammonium group and a monomer not containing a quaternary ammonium group. The arrangement of the repeating units in the copolymer is not particularly limited, and may be any one of an alternating copolymer, a block copolymer, and a random copolymer. When the copolymer is a block copolymer or a random copolymer, the ratio of the repeating unit containing the quaternary ammonium group to the monomer unit of the whole polymer is preferably 20 mol% or more, more preferably 30 mol% or more, and further preferably 40 mol% or more. As repeating units that do not contain a quaternary ammonium group, structures derived from (meth) acrylic acid, (meth) alkyl acrylates, (meth) alkyl acrylates, (meth) acrylate aminoalkyl esters, (meth) acrylamide, styrene derivatives, sulfur dioxide, etc. can be cited.

[0059] <Composition of surface treatment liquid>

[0060] The surface treatment solution is prepared by dissolving the above components in water. As water, water from which ionic substances and impurities have been removed is preferred, and for example, ion exchange water, pure water, ultrapure water, etc. are suitably used. As a solvent, a mixed solvent of an organic solvent having miscibility with water, such as ethanol, isopropanol, and water can also be used.

[0061] The surface treatment liquid may contain components other than those mentioned above. Examples of other components include complexing agents, surfactants, stabilizers, and silane coupling agents.

[0062] The concentration of the water-soluble copper salt in the surface treatment solution is preferably 0.05 mM or more. The concentration of the water-soluble copper salt (divalent copper ions in the solution) is 0.05 mM or more, which can improve the surface treatment efficiency of copper and form a surface with high bonding properties to tin. The concentration of the water-soluble copper salt is preferably 0.1 mM or more, and can also be 0.3 mM or more, 0.5 mM or more, or 1 mM or more.

[0063] On the other hand, when the concentration of the water-soluble copper salt is too high, the bonding property to tin is not sufficiently improved, so the concentration of the water-soluble copper salt in the surface treatment solution is preferably 70 mM or less, more preferably 50 mM or less, further preferably 40 mM or less, and may be 30 mM or less or 20 mM or less. When the concentration of the water-soluble copper salt is high, it is believed that the etching rate of copper caused by the divalent copper ions in the solution is large, which hinders the formation of the coating film, so the bonding property to tin is not sufficiently improved.

[0064] The concentration of the thio compound in the surface treatment solution is preferably 0.005 mM or more, and may be 0.01 mM or more, or 0.02 mM or more. It is believed that the thio compound having a structure in which a nitrogen atom and a sulfur atom are covalently bonded to one carbon atom coexists with the divalent copper ion, and the thio compound is used as a chelating agent for copper to form a coating film on the copper surface.

[0065] Even if the copper surface is treated with a solution that does not contain a thio compound, the bonding to tin is hardly improved, but by treating the copper surface with a solution containing a water-soluble copper salt plus a trace amount of a thio compound, the bonding to tin is greatly improved. On the other hand, when the concentration of the thio compound is too high, the bonding to tin is not sufficiently improved. Therefore, the concentration of the thio compound in the surface treatment solution is preferably 20 mM or less, more preferably 10 mM or less, further preferably 5 mM or less, and may also be 3 mM or less, 2 mM or less, or 1 mM or less.

[0066] From the perspective of promoting surface treatment of copper (forming a coating on the surface) and improving bonding to tin, the molar concentration of the water-soluble copper salt is preferably 0.05 to 500 times the molar concentration of the sulfide compound, and may also be 0.1 to 300 times, 0.5 to 200 times, or 1 to 150 times.

[0067] The concentration of the nitrogen-containing alkaline compound in the surface treatment solution is not particularly limited, but from the viewpoint of surface treatment efficiency, it is preferably 0.01 g / L or more, and may be 0.05 g / L or more, 0.1 g / L or more, 0.5 g / L or more, or 1 g / L or more. From the viewpoint of water solubility of the compound, the concentration of the nitrogen-containing alkaline compound is preferably 50 g / L or less, more preferably 30 g / L or less, and may be 20 g / L or less, or 10 g / L or less.

[0068] Even when the copper surface is treated with a solution containing a water-soluble copper salt and a thio compound and not containing a nitrogen-containing base compound, the bonding property to tin is improved, but the degree of effect is limited. By treating the copper surface with a solution containing a water-soluble copper salt and a thio compound plus a nitrogen-containing base compound, the bonding property to tin is significantly improved. It is believed that the nitrogen-containing base compound acts like a stabilizer, maintaining the concentration of each component near the copper surface, and promoting the surface treatment.

[0069] The pH of the surface treatment solution is not particularly limited. From the perspective of suppressing the insolubilization of the copper salt and improving the surface treatment efficiency, the pH of the surface treatment solution is preferably 10 or less, and may be 9 or less, 8 or less, or 7 or less. From the perspective of solution stability and operability, the pH of the surface treatment solution is preferably 0 or more, and may be 1 or more, or 2 or more. In order to adjust the pH of the solution, a pH adjuster (acid or base) may be added to the surface treatment solution.

[0070] [Surface treatment of copper and formation of copper-tin joint]

[0071] The surface treatment of copper is performed by bringing the solution into contact with the surface of copper and drying and removing the solvent. Copper may be pure copper or a copper alloy. Examples of copper components include copper foil (electrolytic copper foil, rolled copper foil), copper plating films (electroless copper plating films, electrolytic copper plating films), and copper steel. Examples of parts having copper components include electronic substrates such as semiconductor substrates and printed wiring boards, and lead frames.

[0072] If necessary, the copper surface is washed with an acid or the like, and then the copper surface is contacted with the solution to treat the copper surface. Examples of methods for contacting the solution with the copper surface include immersion, spraying, and bar coating.

[0073] The solution is kept in contact with the copper surface for about 2 seconds to 5 minutes. The temperature of the solution at this time is preferably about 10°C to 50°C, more preferably about 15°C to 35°C. During the immersion treatment, shaking may be performed as needed. If necessary, washing with pure water or the like may be performed and then drying may be performed.

[0074] The copper and tin are bonded to form a copper-tin bonded body by hot pressing the tin member to the surface treated copper member. The tin may be pure tin or a tin alloy such as solder. The tin member bonded to the copper surface is typically a plated layer of tin or a tin alloy, or may be a member having a tin plated layer partially formed at the bonding portion with the copper of the connection terminal.

[0075] If heating and pressurization are performed in a state where the surface-treated copper is in contact with the tin-plated layer, an alloy layer is formed on the interface, so that the copper and tin are bonded. Although the heating temperature is not particularly limited, from the viewpoint of promoting the formation of an alloy layer at the interface, it is preferably above 150°C, more preferably above 200°C, and particularly preferably above the melting point of tin (232°C). In the case of a low-melting-point tin alloy, heating can also be performed at a temperature lower than the melting point of tin. Although the upper limit of the heating temperature is not particularly limited, it is generally below 500°C, and can also be below 400°C, below 350°C, or below 300°C.

[0076] Generally, when copper and tin are bonded, a method of forming a tin plating layer on the copper surface to bond the tin and tin to each other or a method of applying a flux on the copper surface or the tin surface to promote the formation of a copper-tin alloy is adopted. By treating the copper surface with the solution, the formation of a copper-tin alloy by thermal compression bonding is promoted even without these treatments, so that copper and tin can be firmly bonded.

[0077] [Example]

[0078] Hereinafter, the present application will be described in more detail based on Examples and Comparative Examples, but the present application is not to be construed as being limited to the following Examples.

[0079] [Solution preparation]

[0080] The components shown in Table 1 were dissolved in ion exchange water so as to have predetermined blending amounts (concentrations) to prepare aqueous solutions. The details of polymers 1 to 4 in Table 1 are as follows.

[0081] <Polymer 1>

[0082] In a four-necked flask equipped with a stirring blade, a thermometer, and a reflux cooling tube, 100 parts by weight of ion exchange water and 20 parts by weight of isopropanol were added as a solvent, 100 parts by weight of 60% triallylethylammonium ethyl sulfate was added as a monomer, 1.5 parts by weight of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] dihydrate was added as a polymerization initiator, and the temperature was raised to about 70°C over 20 minutes. After heating at 70°C for 2 hours, 30 parts by weight of ion exchange water and 1.5 parts by weight of the polymerization initiator were added, and the mixture was further heated at 70°C for 3 hours. Isopropanol was distilled off under reduced pressure. After cooling, ion exchange water was added to obtain a 30% by weight solution of polymer 1.

[0083] <Polymer 2>

[0084] In a four-necked flask equipped with a stirring blade, a thermometer and a reflux cooling tube, 100 parts by weight of ion exchange water and 20 parts by weight of isopropanol were added as a solvent, 100 parts by weight of 60% diallyldimethylammonium chloride was added as a monomer, 4.5 parts by weight of ammonium persulfate was added as a polymerization initiator, and the temperature was raised to about 70°C over 20 minutes. After heating at 70°C for 2 hours, 45 parts by weight of ion exchange water and 4.5 parts by weight of polymerization initiator were added, and the mixture was further heated at 70°C for 3 hours. The isopropanol was distilled off under reduced pressure. After cooling, ion exchange water was added to obtain a 30% by weight solution of polymer 2.

[0085] <Polymer 3>

[0086] An alternating copolymer of diallyldimethylammonium and sulfur dioxide having the following repeating units ("PAS-A-1" manufactured by Nittobo Medical Co., Ltd., weight average molecular weight 5000)

[0087]

[0088] <Polymer 4>

[0089] A random copolymer of vinylpyrrolidone and N,N-dimethylaminoethylmethacrylamide diethylsulfate having the following structure ("HC polymer 2" manufactured by Osaka Organic Chemical Industry, weight average molecular weight about 80,000)

[0090]

[0091] [evaluate]

[0092] (Surface treatment of copper-plated sheets)

[0093] A 25 mm x 25 mm copper-plated plate was immersed in a 5% sulfuric acid aqueous solution for 60 seconds and acid-washed, then washed with water and dried to produce a test piece. The test piece was immersed in the solution (25° C.) in Table 1 for 60 seconds to perform copper surface treatment. The test piece was taken out of the solution, washed with water and dried.

[0094] A 10mm×10mm stencil plate with 20 (4 columns×5 rows) holes with a diameter of 1mm is placed in the center of the surface of the surface treated test piece. Ten solder balls with a diameter of 0.76mm ("Sparkle ball S" manufactured by Senju Metal Industry, Sn: 100%) are alternately arranged at the positions of the holes of the stencil plate so that they contact the treated test piece. The test piece with the stencil plate and 10 solder balls is placed on a hot plate heated to 270°C and heated for 30 seconds. The solder balls are thermally pressed onto the surface of the test piece by the weight of the solder balls and the heating of the hot plate.

[0095] The heated sample is placed on a horizontal table, and after removing the stencil from the test piece, the solder balls are lifted up one by one with tweezers. At this time, the sample that does not fall off the test piece (and the solder ball bonded thereto) and can be lifted up together with the solder ball is considered to have good bonding, and the number of such samples is calculated.

[0096] The above test was carried out three times for one treatment solution, and the total number of copper-plated boards that could be lifted up with the solder ball without falling off was used as the bondability score. The full score of the score is 30 points, and the larger the number, the higher the bondability of the solder ball to the copper surface.

[0097] Table 1 shows the compositions and evaluation results of the solutions of Examples and Comparative Examples.

[0098] [Table 1]

[0099]

[0100]

[0101] In Examples 1 to 10, in which the surface treatment was performed with a solution containing a basic amino acid, a guanidine compound, or a quaternary ammonium salt as a nitrogen-containing base compound in addition to a water-soluble copper salt and a thio compound, the bondability score was above 20, and the solder ball was hot-pressed to the treated copper surface, showing good bondability.

[0102] In Comparative Example 3 which does not contain a thio compound, the bonding score is 0, and the bonding of tin to the copper surface is extremely poor. The same is true for Comparative Example 4 which uses thiosulfuric acid which is a thio compound containing no nitrogen. In addition, in Comparative Example 5 which uses cysteamine which is a thio compound in which a nitrogen atom and a sulfur atom are bonded to different carbon atoms, the score is 1, and similarly to Comparative Examples 3 and 4, the bonding of tin to the copper surface is poor.

[0103] In Comparative Example 6 not containing a water-soluble copper salt, Comparative Example 4 containing an aluminum salt but not containing a water-soluble copper salt, and Comparative Example 7 in which the thio compound does not contain a nitrogen atom, the score is 0 and the bonding is extremely poor. In Comparative Example 8 not containing a nitrogen-containing base compound, the score is 6, which is good compared with Comparative Examples 3 to 7, but is still insufficient compared with Examples 1 to 10.

[0104] From these results, it is considered that a water-soluble copper salt and a thio compound having a structure in which a nitrogen atom and a sulfur atom are bonded to one carbon atom are essential for improving the bonding property of the copper surface to tin, and that further inclusion of a nitrogen-containing basic compound promotes surface treatment (film formation).

[0105] Comparative Example 1, in which the concentration of the water-soluble copper salt is 100 mM, and Comparative Example 2, in which the concentration of the thio compound is 26.3 mM, have low scores and insufficient bonding. From the comparison of Example 5 with Comparative Examples 1 and 2, it can be seen that when the concentrations of the water-soluble copper salt and the thio compound are high, a sufficient bonding improvement effect cannot be obtained.

Claims

1. A copper surface treatment solution, which is an aqueous solution, comprising: Water-soluble copper salts; Thio compounds have a structure in which one or more nitrogen atoms and one or more sulfur atoms are covalently bonded to one carbon atom; and The nitrogen-containing base compound is one or more selected from a basic amino acid, a guanidine compound, and a quaternary ammonium salt; The concentration of the water-soluble copper salt is 0.05 mM to 70 mM; The concentration of the thio compound is 0.005 mM to 20 mM.

2. The surface treatment liquid according to claim 1, characterized in that: The molar concentration of the water-soluble copper salt is 0.05 to 500 times the molar concentration of the thio compound.

3. The surface treatment liquid according to claim 1 or 2, characterized in that: The nitrogen-containing base compound is a quaternary ammonium salt polymer with a molecular weight of more than 1000.

4. A method for surface treatment of copper, wherein: The surface treatment liquid according to claim 1 or 2 is brought into contact with the surface of copper.

5. A method for bonding copper and tin, wherein: The copper is surface treated by the method of claim 4, and the tin member is thermally compressed to the treated surface.

6. A method for producing a copper-tin joint, wherein: The copper is surface treated by the method of claim 4, and the copper and the tin are bonded by thermocompression bonding a tin member to the treated surface.

Citation Information

Patent Citations

  • To-resin adhesive layer and manufacturing method of laminate using it

    JP2008109111A

  • Substrate unit, manufacturing method thereof, and manufacturing method of semiconductor device

    JP2021190473A

  • Coating film-forming composition, method for producing surface-treated metal member, and method for producing metal-resin composite

    JP2022020415A